Evaluasi Program Kesehatan Ibu dan Anak (KIA) pada Ibu Hamil di Puskesmas Peot, Kelurahan Satar Peot, Kecamatan Borong, Kabupaten Manggarai Timur - Waldetrudis Noni; William Djani; Made Ngurah Demi Andayana; Ernestus Holivil (Student Scientific Creativity Journal, 2026)
This study aims to evaluate the implementation of the Maternal and Child Health (MCH) Program for pregnant women at Peot Community Health Center, Borong District, East Manggarai Regency. The study employed a qualitative approach with a case study design and utilized the CIPP (Context, Input, Process, Product) evaluation model. Informants consisted of the Head of the Health Center, MCH Program Coordinator, healthcare workers, and pregnant women selected through purposive sampling. Data were collected through interviews, observations, and documentation and analyzed using the Miles and Huberman interactive model. The findings indicate that, in the context dimension, the MCH Program is highly relevant to community needs and addresses maternal health issues such as anemia, chronic energy deficiency, and high-risk pregnancies. In terms of input, the program is supported by adequate human resources, healthcare facilities, and an innovative funding scheme known as the Seuntais Movement. Regarding the process dimension, the program has been implemented in accordance with healthcare service standards through several innovations, including the Pregnant Women Companion Midwife Program, partnerships between midwives and traditional birth attendants, the Lonto Leok community forum, and the Stunting and Maternal Mortality Alert System. In the product dimension, antenatal care coverage reached 100% during 2022–2024 and contributed to maintaining zero maternal mortality in recent years. However, child health examination coverage remains between 82% and 86%, indicating the need for further improvement.